Investıgatıon of Removal of Dye from Aqueous Solutıon by Advanced Treatment - Cebeci, M. Sarioglu; Selcuk, S.F. (European Scientific Journal, ESJ, 2017)
The textile dyeing and finishing industry use a significant amount of water and produce water pollution. Conventional biological treatment processes have some difficulties for degradation of nonbiodegradable compounds. Dye-bearing wastewaters have high COD and colour. In this study, a photo reactor process was used to remove color from aqueous solution.Effects of pH on Reactive Red 4 and cationic dye removal using 1g/L TiO2, as catalyst were studied at constant inital dye concentration (25 mg/l). Cationic dye removal efficiency is better than Reactive dye removal efficiency for photocatalytic oxidation in this study